Learning Approaches Based on Student Characteristics in the Thought of Abuddin Nata: A Conceptual Study - Husnul Khotimah; Aufa Qutratu ‘Ain; M. Irfan Luthfi Rangkuti; Yahya Komarudin; Mu'arif Mu'arif; Fatoni Achmad; Syaiful Dinata; Amirul Syafiq (AL-ISHLAH: Jurnal Pendidikan, 2025)
Learning approaches that align with students’ individual characteristics are essential for effective education, particularly within Islamic educational contexts. Abuddin Nata, a prominent Indonesian Islamic education scholar, emphasizes the need to adapt instructional strategies based on student diversity in age, potential (fitrah), and intelligence levels. This study employs qualitative library research using content analysis of primary works by Abuddin Nata and relevant secondary literature. Key themes were identified through systematic documentation and thematic categorization of concepts related to learner characteristics and learning models. Nata identifies three fundamental student characteristics—age, innate potential, and intelligence—as determinants in choosing appropriate learning strategies. He proposes three adaptive approaches: individual learning, group learning, and a blended approach. His framework encourages the integration of Islamic values with student-centered pedagogy, emphasizing the importance of balancing personal development and social responsibility. Comparative analysis reveals parallels with contemporary theories such as Piaget’s cognitive development, Vygotsky’s social constructivism, and Gardner’s multiple intelligences. Nata’s model offers a value-based and context-sensitive perspective on differentiated instruction. While philosophically and pedagogically robust, its empirical implementation remains limited, especially in technology-mediated environments. His approach provides practical insights for educators and curriculum developers in designing inclusive and adaptive Islamic learning environments that respond to learner diversity.